Robert Venturi and His Contributions to Postmodern Architecture. - Kahl, Douglas (My University, 2008)
This paper examines the major contributions of architect Robert Venturi to the field of Postmodern architecture during the 1970s. Many of Venturi’s buildings were small in stature, designed for a specific location and site, and only large when necessary. Designing for a specific site was not traditionally done during the first half of the 20th century. The Modern movement was a stark, plain, and disengaging form of architecture from which Venturi took enormous strides to distance himself. Venturi’s interpretations of what Postmodernism should be included intense historical symbolism from the particular region in which he intended to build. For him, a schoolhouse being designed for the state of Georgia ought to be different from a school being designed for Washington state. The cultural history that a community’s citizens share varies intensely from city to city, a realization that Venturi worked to address through Postmodernism. Eventually fed up with the generic feel Modernism projected, Venturi took the quote “Less is more” from Mies van der Rohe, a staunch Modernist architect, and mockingly declared that “Less is a bore.” Venturi’s brand of Postmodern architecture was anything but boring.
Oshkosh Scholar, Volume 3, 2008 pp. 55-63
Keywords: Venturi, Robert; Postmodern architecture; Civilization, Classical; Architecture and society; Artists and architects